PATHOPHYSIOLOGICAL REASONING OF THE EFFICIENCY OF ANTI-ANGIOGENIC THERAPY IN THE RETINAL VEIN OCCLUSION BY THE COHERENT EYE TOMOGRAPHY - V. Yu. Mykhaylichenko; A. S. Ivashchenko; S. A. Samarin; S. A. Volik (Кубанский научный медицинский вестник, 2018)
Aim. The main aim of our research is to study the effectiveness of anti-VEGF therapy in the treatment of retinal vein occlusions.Materials and methods. The study included 124 patients aged between 23 to 66, an average of 54.3±8.9 years old who were on an outpatient and inpatient treatment in the ophthalmologic department of the V.K. Gusak Institute of Emergency and Reconstructive Surgery from 2011 to 2016. We have formed two groups. The comparison group included 66 patients who received standard therapy in the form of local anticoagulant and anti-edematous therapy, disaggregants. To improve microcirculation and with a decongestant purpose, rheopolyglucin was administered intravenously, and intramuscular injections of actovegin were prescribed with an antihypoxic purpose. With edema of the macula and the development of newly formed vessels – laser coagulation, intravitreal or subtenon introduction of trimacionolone. The main group included 58 patients who, in addition to standard therapy, were given the drug Eilia (aflibercept) intravitreally 2 mg in 0.05 ml. Treatment with aflibercept for intravitreal injections started with one injection once a month for the next five months, with a further transition to one injection every two months, with no monitoring required between the injections.Results. When post-thrombotic neovascular glaucoma occurred, the concentration of TGFα in the lacrimal fluid increased by 1.7, and TGFβ by 28-fold. When the branch of the central vein of the retina is occluded according to the ischemic type, the systolic and diastolic blood flow velocity in the retina decreases. With coherent optical tomography with the function of angiography, admission in both groups showed significant macular edema, non-perfusion zones of the retina, a decrease in the density of the capillary network in the inner layers of the retina in angio-OCT, and 3 patients with angio-OCT visualized newly formed vessels in the nonperfusion zone.Conclusion. In the group with the use of anti-angiogenic drugs, earlier restoration of the visual fields and reduction of neoangiogenesis were noted.